Assessment of the practices and contributions of China's green industry to the socio-economic development. (1st June 2017) - Chen, Wenhui; Chen, Jiancheng; Xu, Danyun; Liu, Junchang; Niu, Nana
Abstract: The concept of a green economy has been advocated globally ever since it was first proposed. In China, green economy has been adopted as the national strategy for future economic development. In this paper, we applied statistical description, grey correlation, proportion and elastic coefficient analysis to assess contributions of green industry to the national development from 2008 to 2012. We found that: (1) The average green degree of China's economic industry, 45%, was relatively low. The relative green degrees from high to low were 65% for service industry, 55% for agriculture industry, and 24% for manufacturing industry, respectively. (2) The share that added values of green industry took up gross domestic product (GDP) was between 41% and 48%. Green industry growth was highly correlated to the national economic growth evidenced by their grey correlation coefficient of 0.8532. (3) Both categories and quantities of green products were increasing annually and the growth rate of exported green products exceeded 50% during the study period. The gross domestic product grew by 0.04% owing to the increase of 1% in green product exports. (4) The pulling effect of green industry on employment was not significant, with a contribution rate of about 8%. With governmental support, green industry has made big improvements but there is still a lot of space for it to grow in the long term and it requires greater attention from managers and decision-makers in order to make more contribution to the society and the economy. Highlights: We found out green degree of China's national economic industry was 45%. China's green industry growth was highly correlated to the national economic growth. The pulling effect of China's green industry on employment was not significant. China's green industry reduced pollution emissions and saved energy resources gradually.